Performance evaluation on multi-scenario urban ventilation corridors based on least cost path - Yunhao Fang; Kangkang Gu; Zhao Qian; Zhen Sun; Yongzheng Wang; Ai Wang (Journal of Urban Management, 2021)
Ventilation Corridor is an important technique to mitigate local climate problems. Evaluating the benefits of ventilation corridors has gradually become the standard of its construction in cities. Previous studies have often analyzed the volume of ventilation from the perspective of geometric morphology, while there is a lack of discussion on its performance. Therefore, this study innovatively combined the roughness length (Z0), 3-dimensional aerodynamics parameter, with NDVI and M-NDWI, 2-dimensional indices of land cover through the combination of remote sensing inversion and urban morphology analysis. Compared with the traditional ventilation method, the composite indicator could not only guarantee ventilation volume, but also consider the cooling benefits brought by waters and vegetated areas. In detail, this study was contextualized in four districts in the city core of Hefei, Anhui Province, China. Based on the method of least cost path, we set up four different schemes for comparison, including roughness, roughness~​+~​vegetated areas, roughness~​+~​waters, and roughness~​+~​vegetated areas~​+~​waters. Comparative results were effectively verified through land surface temperature retrieved from the Landsat Thematic Mapper. Results were as follows: (1) Different scenarios exerted different impacts on urban ventilation. Of the four regions, the ventilation corridor that only considers Z0 presented the highest average land surface temperature. (2) The general temperature of ventilation corridors along the path of Z0~​+~​NDVI~​+~​M-NDWI was respectively 34.11~​êC, 31.73~​êC, 34.80~​êC, and 34.93~​êC, presenting a lowest temperature compared with other scenarios of the same region. (3) Among the four regions, ventilation corridors constructed based on the path of Z0~​+~​M-NDWI presented a slightly lower temperature that those based on Z0+NDVI, with respective data of 34.22~​êC~​<~​34.55~​êC, 31.85~​êC~​<~​31.91~​êC, 34.81~​êC~​<~​34.82~​êC, and 35.21~​êC~​<~​35.38~​êC. The results provided methods and evidence for performance evaluation on urban land surface ventilation corridors.
Keywords: 710; Heat island effect; Least cost path (LCP); Vegetated areas; Ventilation corridor; Waters